Enhancement of Pathogen Resistance in Common Bean Plants by Inoculation With Rhizobium etli - Díaz-Valle, Armando; López-Calleja, Alberto Cristian; Alvarez-Venegas, Raúl (Frontiers in Plant Science, 2019)
Symbiotic Rhizobium-legume associations are mediated by exchange of chemical signals that eventually result in the development of a nitrogen-fixing nodule. Such signal interactions are thought to be at the center of the plants’ capacity either to activate a defense response or to suppress the defense response to allow colonization by symbiotic bacteria. In addition, the colonization of plant roots by rhizobacteria activates an induced condition of improved defensive capacity in plants known as induced systemic resistance, based on “defense priming,” which protects unexposed plant tissues from biotic stress.Here, we demonstrate that inoculation of common bean plants with Rhizobium etli resulted in a robust resistance against Pseudomonas syringae pv. phaseolicola. Indeed, inoculation with R. etli was associated with a reduction in the lesion size caused by the pathogen and lower colony forming units compared to mock-inoculated plants. Activation of the induced resistance was associated with an accumulation of the reactive oxygen species superoxide anion (O2−) and a faster and stronger callose deposition. Transcription of defense related genes in plants treated with R. etli exhibit a pattern that is typical of the priming response. In addition, R. etli–primed plants developed a transgenerational defense memory and could produce offspring that were more resistant to halo blight disease. R. etli is a rhizobacteria that could reduce the proliferation of the virulent strain P. syringae pv. phaseolicola in common bean plants and should be considered as a potentially beneficial and eco-friendly tool in plant disease management.